2006
DOI: 10.1002/ijc.22040
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus‐mediated tBid overexpression results in therapeutic effects on p53‐resistant hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide with a very high mortality. Because the success of the conventional therapies is limited, gene therapy may represent an alternative for HCC management. Our earlier study has shown that Bid plays a role in the development of HCC. The aim of our study is to evaluate the possibility of using truncated Bid (tBid) as a novel therapy for HCC treatment. Two HCC cell lines, Hep3B and PLC/ PRF/5, were used in the experiment. Hep3B was a p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…[11][12][13][14] Our previous in vitro study showed that the application of Ad/AFPtBid specifically killed Hep3B cells that are known to produce AFP, and significantly sensitized Hep3B cells to 5-FU and Dox. 20,21 In this study, we confirmed that Ad/AFPtBid could specifically suppress the AFP-producing HCC but not attack non-AFP-producing tumor in an orthotopic mouse model. Application of Ad/AFPtBid can significantly increase the effect of other chemotherapeutic agents such as 5-FU, resulting in a synergistic interaction between Ad/AFPtBid and 5-FU in our model.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…[11][12][13][14] Our previous in vitro study showed that the application of Ad/AFPtBid specifically killed Hep3B cells that are known to produce AFP, and significantly sensitized Hep3B cells to 5-FU and Dox. 20,21 In this study, we confirmed that Ad/AFPtBid could specifically suppress the AFP-producing HCC but not attack non-AFP-producing tumor in an orthotopic mouse model. Application of Ad/AFPtBid can significantly increase the effect of other chemotherapeutic agents such as 5-FU, resulting in a synergistic interaction between Ad/AFPtBid and 5-FU in our model.…”
Section: Discussionsupporting
confidence: 73%
“…AFP promoter was inserted to generate liver cancer cell-specific gene expression. 20 Recombinant adenoviruses have gained increasing usage in gene therapy because the vector system combines a high rate of gene transduction that is not cell cycle dependent and the safety of transient expression. 32 Bid is a pro-apoptotic …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations